2016
DOI: 10.3389/fmech.2016.00001
|View full text |Cite
|
Sign up to set email alerts
|

A Simple Fabrication Process Based on Micro-masonry for the Realization of Nanoplate Resonators with Integrated Actuation and Detection Schemes

Abstract: In this work, we use the micro-masonry technique to fabricate nanoplate resonators with integrated electrostatic actuation and capacitive detection in a few steps. Our approach is an alternative solution to the current fabrication methods used to create membranes and plates that usually rely on the selective etching of a sacrificial layer. Highly doped silicon plates were transfer printed using microtip elastomeric stamps onto insulated bases displaying cavities in order to form suspended structures with airti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Those nanoplate resonators were tested by measuring their resonant frequency in a fully integrated manner. The results indicated that they performed as predicted by theory, and provided quality factors of more than 30 in air [106].…”
Section: Mems Via Micro-legomentioning
confidence: 80%
See 1 more Smart Citation
“…Those nanoplate resonators were tested by measuring their resonant frequency in a fully integrated manner. The results indicated that they performed as predicted by theory, and provided quality factors of more than 30 in air [106].…”
Section: Mems Via Micro-legomentioning
confidence: 80%
“…The structural integrity of nanoplates ensured by micro-LEGO allowed the fabrication of multiple suspended nanoplates in a single step and on the same single base, without mechanical crosstalk between them [105]. After the structural design was further modified and additional interconnects were formed, the nanoplate resonators performed with integrated electrostatic actuation and capacitance-sensing capabilities [106]. Those nanoplate resonators were tested by measuring their resonant frequency in a fully integrated manner.…”
Section: Mems Via Micro-legomentioning
confidence: 99%